2024
DOI: 10.1038/s42003-024-06119-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural reorganization in brain tumors: a machine learning approach using desynchronized functional oscillations

Joan Falcó-Roget,
Alberto Cacciola,
Fabio Sambataro
et al.

Abstract: Neuroimaging studies have allowed for non-invasive mapping of brain networks in brain tumors. Although tumor core and edema are easily identifiable using standard MRI acquisitions, imaging studies often neglect signals, structures, and functions within their presence. Therefore, both functional and diffusion signals, as well as their relationship with global patterns of connectivity reorganization, are poorly understood. Here, we explore the functional activity and the structure of white matter fibers consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…However, our findings (also theirs, Siegel, Snyder, et al, 2016) show that this is a necessary step, and the issues in the frequency domain should be handled separately. Inspiration could be drawn from the literature sudying brain tumors, were it has been found that local and global shifts of the spectrum carry prognostic Park et al (2023) and network Falcó-Roget et al (2024) information.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings (also theirs, Siegel, Snyder, et al, 2016) show that this is a necessary step, and the issues in the frequency domain should be handled separately. Inspiration could be drawn from the literature sudying brain tumors, were it has been found that local and global shifts of the spectrum carry prognostic Park et al (2023) and network Falcó-Roget et al (2024) information.…”
Section: Discussionmentioning
confidence: 99%